Nanoparticles for tumor targeted therapy and preparation method thereof
By designing ultrasound/GSH dual-responsive ZIF-8-GOx@Cu PDA@liposome-LA nanoparticles, the problems of targeted treatments are easily off-targeted, poor treatment effects and inefficient delivery efficiency are solved, and the efficiency and safety of targeted tumor therapy are achieved, which significantly reduces the survival rate of breast cancer cells.
Patent Information
- Application Number
- CN202411134744.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-08-19
AI Technical Summary
In the prior art, targeted treatment is prone to off-target, poor treatment effect and low delivery efficiency, resulting in the ineffectiveness of GOx in the treatment and starvation treatment, and causes inevitable systemic toxicity.
Ultrasound/GSH biresponsive ZIF-8-GOx@Cu PDA@liposome-LA nanoparticles were used to respond to the GSH at the tumor site through the Cu-PDA shell, avoiding the early "off-target" of GOx in normal cells and tissues, and exposing the internal ZIF-8-GOx at the tumor site, activate GOx to catalyze the production of H2O2, and combine ultrasound catalysis and L-arginine reaction to produce NO to achieve multimodal treatment.
The accuracy and efficiency of tumor-targeted treatment are achieved, the damage to normal cells is avoided, the survival rate of breast cancer cells is significantly reduced, and the effective killing of tumor cells is ensured.
Smart Images

Figure CN119112832B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biological nanomaterials, and in particular relates to nanoparticles used for tumor targeted therapy and a preparation method thereof. Background Art
[0002] Cancer, characterized by abnormal cell metabolism and growth of cancer cells, remains a major threat to global human health. The special metabolic pattern of cancer cells (i.e., aerobic glycolysis) makes them more demanding on nutrients, especially glucose, and causes the accumulation of lactic acid in the tumor microenvironment. In recent years, starvation therapy, which "starves" tumor cells by blocking or consuming the supply of nutrients such as oxygen, glucose, lactic acid, and amino acids in the tumor, has become a major research hotspot. Based on the key role of glucose in tumor growth and proliferation and the sensitivity of cancer cells to changes in glucose concentration, glucose oxidase (GOx) has been widely studied in the design of starvation therapy systems by catalyzing the reaction of intracellular glucose and oxygen (O2) to produce hydrogen peroxide (H2O2) and gluconic acid to cut off the nutrient supply of cancer cells and aggravate intracellular hypoxia, acidification, and oxidative stress levels. However, the demand of normal cells for glucose supply and metabolism and the degradation characteristics of GOx by proteases often make GOx "off-target" and ineffective in starvation therapy during treatment, and cause inevitable systemic toxicity, which limits the further application of GOx in biomedicine.
[0003] In the process of realizing the present invention, the inventors found that there are at least the following problems in the prior art: targeted therapy is prone to off-target effects, poor therapeutic effects, and low delivery efficiency. Summary of the invention
[0004] The purpose of the present invention is to provide an ultrasound / GSH dual-responsive ZIF-8-GOx@Cu PDA@liposome-LA nanoparticle and a preparation method and application thereof in view of the deficiencies in the prior art, so as to solve the problems existing in the related art such as easy off-target of targeted therapy, poor therapeutic effect and low delivery efficiency.
[0005] One of the technical solutions of the present invention is to provide a ZIF-8-GOx@Cu-PDA@liposome-LA nanomaterial, which has a three-layer structure: a ZIF-8-GOx core, a Cu-PDA layer and a liposome-LA layer, wherein the ZIF-8-GOx core is ZIF-8 encapsulated with glucose oxidase; in the Cu-PDA layer, copper ions are evenly distributed in polydopamine; in the liposome-LA layer, L-arginine is dispersed in liposomes. The Cu-PDA shell can specifically respond to GSH in the tumor site and cleave, which can avoid GOx from "off-targeting" in normal cells and tissues in advance. After the internal ZIF-8-GOx is exposed at the tumor site, Zn overload is triggered and GOx is activated to catalyze the reaction of intracellular glucose and oxygen to generate H2O2. The consumption of glucose can achieve starvation therapy, and work together with Zn ion therapy to aggravate cellular oxidative stress. H2O2 can also produce more active ROS under ultrasound catalysis. In addition, it can quickly react with L-arginine (LA) delivered by the liposome layer to produce high concentration of NO to achieve ultrasound catalytic gas therapy.
[0006] The second technical solution of the present invention is to provide a method for preparing a ZIF-8-GOx@Cu-PDA@liposome-LA (ZGCLL) nanomaterial, which prepares ZIF-8-GOx by coprecipitation, and uses it as a template to coat the surface with a Cu-PDA shell layer, and on this basis, liposomes and LA are loaded on the surface of ZIF-8-GOx@Cu-PDA (ZGCP). The nanoparticles prepared in this embodiment are spherical and have a particle size of 100-300 nm. Specifically, the present invention adopts the following steps:
[0007] Step 1. Add 10-12 mL of 0.194 g / mL 2-methylimidazole aqueous solution to 4-5 mL of 10 mg / mL GOx solution and stir at room temperature for 20 min. Then add 4 mL of 25 mg / mL Zn(NO3)2‧6H2O aqueous solution to the above solution. After stirring at room temperature for 30 min, add 20 mg of polyether F127 to the reaction system and continue the reaction for 2 h. The reaction product is centrifuged and washed with water for 3-4 times to obtain ZIF-8-GOx nanoparticles.
[0008] Step 2. Add 1-2 mL of 10 mg / mL ZIF-8-GOx nanoparticle dispersion and 100-200 μL of ammonia water to 10-16 mL of a mixed aqueous solution containing 8.75-12.5 mg of dopamine hydrochloride and 2-2.8 g of CuCl2·2H2O, and react for 5 hours in the dark; after the reaction, centrifuge and wash the product with water 3-4 times to obtain ZGCP.
[0009] Step 3. DPPC, cholesterol and DSPE-mPEG are mixed in proportion to form a uniform solution; the uniform solution is added to chloroform and ultrasonically treated with an ultrasonic cleaner, and then evaporated to dryness using a rotary evaporator; the liposome sample is dissolved in water to prepare a liposome solution.
[0010] The mixing mass ratio of DPPC, cholesterol and DSPE-mPEG in the homogeneous solution is 6:4:0.5;
[0011] The ultrasonic treatment time is 10 min;
[0012] Step 4. Mix 1-1.25 mL of 10 mg / mL ZGCP dispersion with 80-100 μL of 0.45 mg / μL liposome solution and 1-1.25 g L-arginine, and perform ultrasonic treatment. Centrifuge and wash with water for 3-4 times to obtain the target product ZGCLL. The final product is spherical particles of 100-300 nm.
[0013] The third technical solution of the present invention is to provide an application of the above-mentioned nanoparticles for preparing a drug for reducing the survival rate of breast cancer cells.
[0014] The prepared drug has a better effect under the synergy of ultrasound. The internal ZIF-8-GOx mediates Zn overload and activates GOx to catalyze the reaction of intracellular glucose and oxygen to produce H2O2. The consumption of glucose can achieve starvation therapy, and work together with Zn ion therapy to aggravate cellular oxidative stress. H2O2 produces more active ROS under ultrasound catalysis, and can also quickly react with the delivered LA to produce high-concentration NO to achieve ultrasound catalytic gas therapy.
[0015] A fourth technical solution of the present invention is to provide a tumor treatment system, comprising:
[0016] The nanoparticles for tumor targeted therapy according to claim 1;
[0017] A drug delivery system for delivering the nanoparticles for tumor targeted therapy according to claim 1;
[0018] An ultrasound system is used to input ultrasound waves.
[0019] Beneficial effects of the present invention: In vitro and in vivo studies have shown that this tumor-specific intelligent multimodal treatment system has precise and efficient anti-tumor performance.
[0020] The present invention can quickly respond to GSH and realize the rapid release of copper ions, and can release 16% of copper ions within 4 hours. The concentration of H2O2 in the solution after the present invention reacts with glucose for 12 hours and 24 hours is 429 μM and 1069 μM respectively. The present invention can produce 2.14 μM NO within 24 hours, and can produce 9.43 μM NO under ultrasonic conditions.
[0021] After the invention is mixed and cultured with mouse breast cancer cells 4T1 and human umbilical vein endothelial cells HUVEC, the survival rate of mouse breast cancer cells 4T1 is 2.6%, while the survival rate of human umbilical vein endothelial cells HUVEC is greater than 85%. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0023] Figure 1 Schematic diagram of the synthesis process of ZIF-8-GOx@Cu-PDA@liposome-LA and the ultrasound / GSH dual-response ion interference / starvation / gas synergistic treatment mechanism in the present invention
[0024] Figure 2 TEM images of ZIF-8-GOx at different magnifications in Example 1;
[0025] Figure 3 TEM images of ZGCP at different magnifications in Example 1;
[0026] Figure 4 is the energy dispersive X-ray spectrum (Cu, N, Zn and O) of ZGCP in Example 1 (scale: 200 nm);
[0027] Figure 5 XRD patterns of ZIF-8-GOx and ZGCP in Example 1;
[0028] Figure 6 (a) XPS full spectrum, (b) Zn 2p XPS spectrum and (c) Cu 2p XPS spectrum of ZGCP in Example 1;
[0029] Figure 7 It is the TEM image of ZIF-8 in Example 1;
[0030] Figure 8 TEM images of ZIF-8@Cu-PDA at different magnifications in Example 1;
[0031] Fig. 9 is the GSH standard curve;
[0032] Fig.10 is the GSH content in ZGCP (1 mg / mL) in Example 1 after reacting with different concentrations of GSH for 1 h;
[0033] Fig.11 (a) UV-Vis curves and (b) GSH quantitative results of the solution after the reaction of GSH (5 mM) with ZGCP (1 mg / mL) in Example 1 for different time periods (0 h, 2 h, 6 h, 12 h and 24 h) detected by the DTNB method;
[0034] Fig.12 are SEM images of ZGCP in Example 1 at different magnifications after reacting with GSH (5 mM) for different times (0 h, 2 h, 6 h, 12 h, and 24 h);
[0035] Fig.13 The Cu ion release of ZGCP in Example 1 after reacting with different concentrations of GSH for different time periods;
[0036] Fig.14 is the H2O2 standard curve;
[0037] Fig.15 The UV-Vis curves of the solution of ZGCP (1 mg / mL) and glucose (1 mg / mL) at different time points (1 h, 2 h, 6 h, 12 h and 24 h) in Example 1;
[0038] Fig.16 (a) UV-Vis curves and (b) H2O2 content of the solution of ZGCP (1 mg / mL) and glucose (1 mg / mL) at different time points (1 h, 2 h, 6 h, 12 h and 24 h) after GSH (5 mM) treatment for 12 h;
[0039] Fig.17 The UV-Vis curve of the solution after ZGCP (1 mg / mL) was treated with PBS at pH = 5.8 for 12 h and reacted with glucose (1 mg / mL) for 12 h;
[0040] Fig.18 TEM images of ZGCLL at different magnifications;
[0041] Fig.19 Energy dispersive X-ray spectra of ZGCLL (Cu, P, Zn, and O) (scale bar: 200 nm);
[0042] Fig. 20 is the XRD pattern of ZGCLL;
[0043] Fig.21 (a) XPS full spectrum, (b) Zn 2p XPS spectrum and (c) Cu 2p XPS spectrum of ZGCLL;
[0044] Fig. 22 The standard curve for detecting GOx by Bradford method;
[0045] Fig.23 (a) UV-Vis curves and (b) GSH quantitative results of the solution after the reaction of GSH (5 mM) and ZGCLL (1 mg / mL) for different time periods (0 h, 2 h, 6 h, 12 h, and 24 h) detected by the DTNB method;
[0046] Fig.24 (a) UV-Vis curves and (b) H2O2 content of the ZGCLL (1 mg / mL) and glucose (1 mg / mL) solutions at different time points (1 h, 2 h, 6 h, 12 h, and 24 h) after GSH (5 mM) treatment for 12 h;
[0047] Fig.25 is the standard curve for NO detection;
[0048] Fig.26 is the NO production of L-arginine (1 mg / mL) at different pH values at different time points;
[0049] Fig. 27 NO production at different time points in a mixed solution of L-arginine (1 mg / mL) and H2O2 (1 mM) under different treatments (1.0 MHz, 1.0 W / cm2, 5 min);
[0050] Fig.28 The mixed solution of ZGCP (1 mg / mL) and glucose (1 mg / mL) treated with L-arginine (1 mg / mL) and GSH (5 mM, 12 h) was subjected to different treatments (1.0 MHz, 1.0 W / cm 2 NO production at different time points under 40°C (5 min);
[0051] Fig.29 The mixed solution of ZGCLL (1 mg / mL) and glucose (1 mg / mL) treated with GSH (5 mM, 12 h) was subjected to ultrasound treatment (1.0 MHz, 1.0 W / cm 2 NO production at different time points under 40°C (5 min);
[0052] Fig.30Cell viability of HUVEC and 4T1 cells after co-culture with different concentrations (0-30 ppm) of (a) ZGCP and (b) ZGCLL;
[0053] Fig.31 is the cell survival rate of 4T1 cells after co-culture with different concentrations of L-arginine (0-500 ppm);
[0054] Fig.32 is the cell survival rate of 4T1 cells after co-culture with different concentrations of ZGCLL with or without ultrasonic treatment (*** p < 0.001, ** p < 0.01 and * p < 0.05, n = 3, mean ± SD);
[0055] Fig.33 Fluorescence images of 4T1 cells treated with different methods after co-staining with Calcein-AM and PI (bar: 100 µm); Fluorescence images of 4T1 cells treated with different methods after co-staining with EdU and Hoechst (bar: 50 µm);
[0056] Fig.34 Cell viability of HUVEC and 4T1 cells after co-culture with different concentrations of ZIF-8@Cu-PDA (ZGCP, 0–500 ppm). DETAILED DESCRIPTION
[0057] The Cu-PDA shell of the present invention can respond to the cleavage of GSH in the tumor site to avoid premature degradation and "off-target" of GOx, specifically act on tumor cells, expose internal ZIF-8 to mediate Zn overload and activate GOx to catalyze the reaction of intracellular glucose and oxygen to generate H2O2, and the consumption of glucose can achieve starvation therapy, and work together with Zn ion therapy to aggravate cell oxidative stress. H2O2 can also produce more active ROS under ultrasonic catalysis, and quickly react with the delivered LA to produce high-concentration NO to achieve ultrasonic catalytic gas therapy.
[0058] The exemplary embodiments will be described in detail below, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following exemplary embodiments do not represent all implementations consistent with the present application. Instead, they are only examples of devices and methods consistent with some aspects of the present application as detailed in the attached claims.
[0059] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0060] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0061] The ammonia water in the present invention is a commercially available product, and the ammonia content is 25% to 27%;
[0062] It should be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only an example within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below. Example 1
[0063] A method for preparing ZIF-8-GOx@Cu-PDA@liposome-LA nanoparticles may include the following steps:
[0064] Step (1), add 10 mL of 0.194 g / mL 2-methylimidazole aqueous solution to 4 mL of 10 mg / mL GOx solution and stir at room temperature for 20 min, then add 4 mL of 25 mg / mL Zn(NO3)2‧6H2O aqueous solution to the above solution. After stirring at room temperature for 30 min, add 20 mg F127 to the reaction system and continue the reaction for 2 h. Wash the reaction product with water by centrifugation for 3-4 times to obtain ZIF-8-GOx nanoparticles, and redisperse in 10 mL deionized water;
[0065] Step (2), dissolving 12.5 mg dopamine hydrochloride and 2.8 mg CuCl2‧2H2O in 10 mL deionized water. Mixing 100 μL ammonia water and 1 mL ZIF-8-GOx solution with a concentration of 10 mg / mL, adding to the above solution and stirring at room temperature in the dark for 5 h. After the reaction is completed, the product is washed three to four times by centrifugation with water to obtain ZGCP, and redispersed in 4 mL deionized water to obtain a ZGCP solution;
[0066] TEM images of the materials obtained in step 1 and step 2 are shown in Figure 2 and Figure 3 From the figure, it can be seen that the synthesized nanomaterials are spherical particles. The XRD spectra of ZIF-8-GOx obtained in step 1 and ZGCP obtained in step 2 are shown in Figure 5 ; The energy dispersive X-ray spectrum obtained by step 2 of this embodiment ( Figure 4 ) and its XPS spectrum ( Figure 6 ) It can be seen that the synthesized material contains copper and zinc, and the copper ions and zinc ions are successfully and evenly distributed in the nanomaterial, proving the successful synthesis of ZGCP.
[0067] The ZGCP obtained in step 2 was added to GSH to test its GSH consumption ability. DTNB (4 mg) was dissolved in buffer solution (1 mL, pH = 8.0) to prepare DTNB solution. ZGCP or ZGCLL solution (1 mg / mL, 1 mL) was mixed with GSH (5 mM), and the supernatant (20 μL) was collected by centrifugation after different reaction times (0 h, 2 h, 6 h, 12 h and 24 h) and mixed with DTNB solution (50 μL) and buffer (2.5 mL, pH = 7.0). After 15 min of reaction, the absorbance at 350 nm-600 nm was recorded using a UV-visible spectrophotometer, and the absorbance at 412 nm was taken to quantify GSH. Fig.10 is the GSH content in the solution after ZGCP (1 mg / mL) reacted with different concentrations of GSH for 1 h in this example; Fig.11 (a) UV-Vis curve and (b) GSH quantitative results of the solution after the reaction of ZGCP (1 mg / mL) and GSH (5 mM) for different time periods (0 h, 2 h, 6 h, 12 h and 24 h). It can be seen that there is a significant consumption of GSH when ZGCP and GSH exist at the same time.
[0068] Then, the ZGCP and GSH obtained in step 2 were mixed and reacted, and SEM images were taken at different times, such as Fig.12 , it can be seen that after reacting with GSH, the shell of ZGCP collapsed and decomposed rapidly, and the particle degradation was obvious, which provided a basis for the exposure of ZIF-8 and GOx and the activation of GOx activity.
[0069] The release of Cu ions in ZGCP after reacting with different concentrations of GSH for different time periods was analyzed by ICP-OES. Fig.13 As shown in the figure, in the first 4 hours, the Cu ions in ZGCP can be rapidly released in response to GSH, and about 16% of the copper ions are released at 4 h, while in the absence of GSH (i.e., 0 mM GSH), almost no copper ions are released.
[0070] The activity of ZGCP in GOx in response to GSH and its ability to induce H2O2 production were studied by 3,3,5,5-tetramethylbenzidine (TMB) color reaction. ZGCP solution (1 mg / mL, 1 mL) was reacted with GSH (5 mM) for 12 h, and the precipitate was collected by centrifugation and redispersed in 2 mL of glucose solution (1 mg / mL). The supernatant was centrifuged at different reaction time points (1 h, 2 h, 6 h, 12 h and 24 h) to detect the production of H2O2. The test solution (200 μL) was mixed with HRP (1U / mL, 300 μL) and PBS buffer (1.5 mL, pH = 5.8) for 10 min, and then TMB ethanol solution (2 mM, 300 μL) was added to the system. The absorbance of the solution from 300 nm to 800 nm was recorded using a UV-visible spectrophotometer, and the H2O2 was quantitatively calculated based on the absorbance at 653 nm. In the presence of H2O2, peroxidase catalyzes the redox reaction between H2O2 and TMB, oxidizing TMB to blue ox-TMB. The concentration of H2O2 can be quantitatively analyzed by detecting the characteristic absorption peak intensity of TMB at 653 nm. Fig.15 As shown in the figure, when ZGCP directly reacted with glucose at different time points, TMB did not show obvious characteristic peaks, which indicated that no obvious H2O2 was produced and ZGCP itself did not show GOx activity. However, after reacting with GSH (5 mM) for 12 h, glucose solution was added to the solution. As the reaction time increased, the absorbance of the characteristic peaks of TMB (at 370 nm and 653 nm) gradually increased, which indicated the time-dependent H2O2 production ( Fig.16 ).
[0071] Step (3), 6 g DPPC, 4 g cholesterol and 0.5 g DSPE-mPEG were mixed uniformly, the uniform solution was added to chloroform and ultrasonically treated for 10 min using an ultrasonic cleaner, and then evaporated to dryness using a rotary evaporator;
[0072] Step (4), dissolving the liposome sample in 4 mL of water to prepare a liposome solution, mixing 80 μL of the 0.45 mg / μL liposome solution, 1 g of L-arginine and 1 ml of a 10 mg / mL ZGCP solution and treating under ultrasound for 10 min;
[0073] Step (5), washing the mixed solution with water by centrifugation for three to four times to obtain the target product ZGCLL nanoparticles.
[0074] Fig.18TEM images of ZGCLL at different magnifications of this embodiment are shown; it can be seen that the ZGCLL has a three-layer structure, is spherical, and has a particle size of 100-300 nm.
[0075] Fig. 20 is the XRD pattern of ZGCLL in this embodiment; Fig.21 : is the XPS spectrum of ZGCLL of this example; the crystal structure of ZGCLL and the successful encapsulation of Zn and Cu ions can be seen.
[0076] Fig.19 : is the energy dispersive X-ray spectrum (Cu, P, Zn and O) of ZGCLL of this example (scale: 200 nm); it can be seen that Zn and Cu ions are uniformly distributed.
[0077] The ZGCLL obtained in step 5 was added to GSH. The (a) UV-Vis curve and (b) GSH quantitative results of the solution after the reaction of GSH (5 mM) and ZGCLL (1 mg / mL) of this example for different time periods (0 h, 2 h, 6 h, 12 h and 24 h) were detected by DTNB method. It can be seen that when this example exists, the GSH content in the solution is significantly reduced, and ZGCLL has a certain GSH consumption capacity.
[0078] The activity of ZGCLL in GOx in response to GSH and its ability to induce H2O2 production were studied by 3,3,5,5-tetramethylbenzidine (TMB) color reaction. ZGCLL solution (1 mg / mL, 1 mL) was reacted with GSH (5 mM) for 12 h, and the precipitate was collected by centrifugation and redispersed in 2 mL of glucose solution (1 mg / mL). The supernatant was centrifuged at different reaction time points (1 h, 2 h, 6 h, 12 h and 24 h) to detect the production of H2O2. The test solution (200 μL) was mixed with HRP (1U / mL, 300 μL) and PBS buffer (1.5 mL, pH = 5.8) for 10 min, and then TMB ethanol solution (2 mM, 300 μL) was added to the system. The absorbance of the solution from 300 nm to 800 nm was recorded using a UV-visible spectrophotometer, and the H2O2 was quantitatively calculated based on the absorbance at 653 nm. In the presence of H2O2, peroxidase catalyzes the redox reaction between H2O2 and TMB, oxidizing TMB to blue ox-TMB. The concentration of H2O2 can be quantitatively analyzed by detecting the characteristic absorption peak intensity of TMB at 653 nm. Fig.24As shown in the figure, the (a) UV-Vis curve and (b) H2O2 content of the solution of ZGCLL in this example at different time points (1 h, 2 h, 6 h, 12 h and 24 h) after being treated with GSH (5 mM) for 12 h. It can be seen that the example itself does not show GOx activity, but after being treated with GSH, the H2O2 concentration in the solution is significantly increased.
[0079] L-arginine, as an intracellular nitric oxide (NO) gas donor, can be catalytically oxidized to NO and L-citrulline under the action of nitric oxide synthase (NOS), and can also generate NO in response to reactive oxygen species such as H2O2. Ultrasound can convert ultrasonic mechanical energy into chemical energy, catalyze H2O2 to produce reactive oxygen species (O·) with higher oxidative activity, thereby more efficiently oxidizing L-arginine molecules to produce more NO. The nitric oxide generation of ZGCLL under ultrasound was detected using a nitric oxide kit. Specifically, ZGCLL solution (1 mg / mL, 1 mL) was reacted with GSH (5 mM) for 24 h and then centrifuged to collect the precipitate. The precipitate was added to glucose solutions (1 mg / mL, 2 mL) with different pH values and subjected to ultrasonic irradiation (1.0 MHz, 1.0 W / cm 2 , 5 min) and quantitative detection of NO. In each well of a 96-well plate, 50 μL of the test solution, room temperature Griess Reagent I, and room temperature Griess Reagent II were added in sequence, and the absorbance was measured at 560 nm using an ELISA reader. The generation of NO in the system was calculated using the standard curve. Fig.29 As shown, GSH-treated ZGCLL can expose the core GOx and react with the added glucose to generate H2O2, which further reacts with L-arginine under ultrasound catalysis to achieve the massive generation of NO.
[0080] In vitro cell experiments were performed on ZGCLL, using HUVEC human umbilical vein endothelial cells and mouse breast cancer cells 4T1 to evaluate the in vitro cell biocompatibility and therapeutic effects of ZGCP and ZGCLL.
[0081] Calcein-AM and PI co-staining were used to mark the live and dead cells after different treatments, and the effects of ZGCP and ZGCLL on the survival rate of 4T1 cells were further evaluated.
[0082] The effects of ZGCP and ZGCLL on the proliferation ability of 4T1 cells were studied by EdU and Hoechst co-staining.
[0083] like Fig.30 As shown, the cell survival rates of HUVEC and 4T1 cells after co-culture with ZGCP and ZGCLL at different concentrations (0-30 ppm) show that the survival rate of HUVEC cells cultured with the ZGCLL nanoparticles of the present invention is improved compared with that of ZGCP without liposome-LA layer coating, while the survival rate of 4T1 cells is less improved, indicating that ZGCLL can reduce the damage to normal cells while maintaining the killing power to tumor cells.
[0084] Fig.33 The fluorescence images of 4T1 cells treated differently after co-staining with Calcein-AM and PI (scale: 100 µm) and the fluorescence images of 4T1 cells treated differently after co-staining with EdU and Hoechst (scale: 50 µm) show that compared with the control group and the ultrasound group alone, the ZGCP group, the ZGCLL group and the ZGCLL+US group all showed significantly weakened green fluorescence, and the proportion of EdU-labeled cells was significantly reduced, indicating that ZGCP, ZGCLL and ZGCLL+US can significantly inhibit the proliferation activity of 4T1 cells. In this example, ZGCLL has the strongest ability to inhibit cell proliferation and induce cell apoptosis when ultrasound is applied.
[0085] Subsequently, the cytotoxicity of a given concentration of ZGCLL on 4T1 under ultrasound treatment was studied: As shown in Figure 32, compared with the group without ultrasound treatment, the application of ultrasound can promote the cell killing effect of ZGCLL on 4T1 to a certain extent, which is related to the fact that ZGCLL catalyzes Zn overload and GOx-induced H2O2 to react with L-arginine to produce NO under ultrasound, thereby inducing NO gas therapy. Example 2
[0086] A method for preparing ZIF-8-GOx@Cu-PDA@liposome-LA nanoparticles may include the following steps:
[0087] Step (1), add 12 mL of 0.194 g / ml 2-methylimidazole aqueous solution to 5 mL of 10 mg / mL GOx solution and stir at room temperature for 20 min, then add 4 mL of 25 mg / mL Zn(NO3)2‧6H2O aqueous solution to the above solution. After stirring at room temperature for 30 min, add 20 mg F127 to the reaction system and continue the reaction for 2 h. Wash the reaction product with water by centrifugation for 3-4 times to obtain ZIF-8-GOx nanoparticles, and redisperse in 10 mL deionized water;
[0088] Step (2), 8.75 mg dopamine hydrochloride and 2 mg CuCl2‧2H2O were dissolved in 16 mL deionized water. 200 μL ammonia water and 2 mL 10 mg / mL ZIF-8-GOx solution were mixed and added to the above solution and stirred at room temperature in the dark for 5 h. After the reaction was completed, the product was washed with water by centrifugation for 3-4 times to obtain ZGCP, and then redispersed in 4 mL deionized water to obtain ZGCP solution;
[0089] Step (3), 12 g DPPC, 8 g cholesterol and 1 g DSPE-mPEG were mixed uniformly, the uniform solution was added to chloroform and ultrasonically treated for 10 min using an ultrasonic cleaner, and then evaporated to dryness using a rotary evaporator;
[0090] Step (4), dissolving the liposome sample in 4 mL of water to prepare a liposome solution with a concentration of 0.45 mg / μL, mixing 100 μL of the liposome solution, 1.25 g of L-arginine and 1.25 mL of a ZGCP solution with a concentration of 10 mg / mL and treating under ultrasound for 10 min;
[0091] Step (5), washing the mixed solution with water by centrifugation for 3-4 times to obtain the target product ZGCLL nanoparticles.
[0092] The samples of this example were studied using the characterization method of Example 1. It was found that the characterization results of the products obtained in this example were similar to those of Example 1, both of which were spherical nanoparticles with a three-layer structure of 100-300 nm. Example 3
[0093] A method for preparing ZIF-8-GOx@Cu-PDA@lipsome-LA nanoparticles may include the following steps:
[0094] Step (1), add 100 mL of 0.194 g / mL 2-methylimidazole aqueous solution to 40 mL of 10 mg / mL GOx solution and stir at room temperature for 20 min, then add 40 mL of 25 mg / mL Zn(NO3)2‧6H2O aqueous solution to the above solution. After stirring at room temperature for 30 min, add 200 mg F127 to the reaction system and continue the reaction for 2 h. Wash the reaction product with water by centrifugation for 3-4 times to obtain ZIF-8-GOx nanoparticles, and redisperse in 100 mL deionized water;
[0095] Step (2), dissolving 87.5 mg of dopamine hydrochloride and 20 mg of CuCl2‧2H2O in 160 mL of deionized water. Mixing 2 mL of ammonia water and 20 mL of a 10 mg / mL ZIF-8-GOx solution, adding the mixture to the above solution and stirring at room temperature in the dark for 5 h. After the reaction is completed, the product is washed with water by centrifugation for 3-4 times to obtain ZGCP, and redispersed in 40 mL of deionized water to obtain a ZGCP solution;
[0096] Step (3), 120 g DPPC, 80 g cholesterol and 10 g DSPE-mPEG were mixed uniformly, the uniform solution was added to chloroform and ultrasonically treated for 15 min using an ultrasonic cleaner, and then evaporated to dryness using a rotary evaporator;
[0097] Step (4), dissolving the liposome sample in 40 mL of water to prepare a liposome solution with a concentration of 0.45 mg / μL, mixing 1000 μL of the liposome solution, 12.5 g of L-arginine and 12.5 ml of a 10 mg / mL ZGCP solution and treating under ultrasound for 15 min;
[0098] Step (5), washing the mixed solution with water by centrifugation for 3-4 times to obtain the target product ZGCLL nanoparticles.
[0099] The samples of this example were studied using the characterization method of Example 1. It was found that the characterization results of the products obtained in this example were similar to those of Example 1, both of which were spherical nanoparticles with a three-layer structure of 100-300 nm.
Claims
1. A nanoparticle for tumor targeted therapy, characterized in that: It has a core-shell structure, and includes, from the inside to the outside, a ZIF-8-GOx core, a Cu-PDA layer, and a liposome-LA layer, wherein the ZIF-8-GOx core is ZIF-8 encapsulating glucose oxidase; in the Cu-PDA layer, copper ions are evenly distributed in polydopamine; in the liposome-LA layer, L-arginine is dispersed in the liposome.
2. The nanoparticles for tumor targeted therapy according to claim 1, characterized in that: The nanoparticles are spherical and have a particle size of 100-300 nm.
3. A method for preparing nanoparticles according to claim 1, characterized in that: include: A Cu-PDA layer was coated on the outside of ZIF-8-GOx to form ZGCP; And, a liposome layer is coated on the outside of ZGCP to obtain ZGCLL nanoparticles.
4. The preparation method according to claim 3, characterized in that: ZIF-8-GOx was prepared by the following method: 10-12 mL of 0.194 g / mL 2-methylimidazole aqueous solution was added to 4-5 mL of 10 mg / mL GOx solution and stirred at room temperature for 20 min. Then, 4 mL of 25 mg / mL Zn(NO3)2‧6H2O aqueous solution was added to the above solution. After stirring at room temperature for 30 min, 20 mg of polyether F127 was added to the reaction system and the reaction was continued for 2 h. The reaction product was centrifuged and washed with water for 3-4 times to obtain ZIF-8-GOx nanoparticles.
5. The preparation method according to claim 3, characterized in that: The method of coating the ZIF-8-GOx with a Cu-PDA layer specifically includes: adding 1-2 mL of a 10 mg / mL ZIF-8-GOx nanoparticle dispersion and 100-200 μL of ammonia water to a 10-16 mL mixed aqueous solution containing 8.75-12.5 mg of dopamine hydrochloride and 2-2.8 g of CuCl2·2H2O, and reacting for 5 hours in the dark; after the reaction, the product is centrifuged and washed with water for 3-4 times to obtain ZGCP.
6. The preparation method according to claim 3, characterized in that: The liposomes coated on the outside of ZGCP specifically include: 1~1.25mL of 10mg / mL ZGCP dispersion was mixed with 80~100μL of 0.45mg / μL liposome solution and 1~1.25g L-arginine, and then subjected to ultrasonic treatment; the target product ZGCLL was obtained by centrifugation and washing with water for 3-4 times.
7. The preparation method according to claim 6, characterized in that: The liposome solution was prepared by the following method: DPPC, cholesterol, and DSPE-mPEG were mixed in a mass ratio of 6:4:0.5 to form a homogeneous solution; the homogeneous solution was added to chloroform and subjected to ultrasonic treatment, and then evaporated to dryness using a rotary evaporator.
8. The preparation method according to claim 7, characterized in that: The ultrasonic treatment time is 10 minutes.
9. Use of the nanoparticles according to claim 1 for preparing a drug for reducing the survival rate of breast cancer cells.
10. A tumor treatment system, characterized in that: include: The nanoparticles for tumor targeted therapy according to claim 1; A drug delivery system for delivering the nanoparticles for tumor targeted therapy according to claim 1; An ultrasound system is used to input ultrasound waves.